Quality of Life Assessment after Canal Wall Down Mastoidectomy: Our Experiences in Shaheed Ziaur Rahman Medical College Hospital, Bogura - Alam, Md Khorsed; Md Saiduzzaman, -; Rahman, Md Asadur; Islam, Syed Sanaul; Rahman, Mohammad Anisur; Sarker, Kanchan Kumar (Bangladesh Journal of Otorhinolaryngology, 2021)
Objective: To determine subjective outcomes after cholesteatoma surgery. Design: Cross sectional observational study Methods: Study place: Shaheed Ziaur Rahman Medical college Hospital (SZMCH), Bogura, Bangladesh Study population: Chronic otitis media (COM) with extensive cholesteatoma. Interventions: Canal wall down mastoidectomy for cholesteatoma. Main Outcome Measures: In this study, the Chronic Ear Survey (CES) was provided to all patients preoperatively and one year after surgery. The preoperative and postoperative score differences were analyzed. We also assessed correlations between chronic ear survey scores and air conduction threshold. Results: Seventy six patients were enrolled in our study & marked improvements were found in total CES score & all subscale scores postoperatively (P value: 0.00). The total CES score and symptom subscale scores were observed greater improvement (P value: 0.00).Significant negative linear correlations were observed among total CES scores, symptom subscale scores and air conduction thresholds (P<.05). Conclusion: The present study suggests that canal wall down mastoidectomy (CWDM) provides a significant improvement in the post-operative Quality of life (QoL) &b there is a significant association between subjective outcomes &the objective audiometric results. Bangladesh J Otorhinolaryngol; April 2021; 27(1): 52-58